2018
DOI: 10.7717/peerj.5486
|View full text |Cite
|
Sign up to set email alerts
|

A bioinformatics approach to identifyingWolbachiainfections in arthropods

Abstract: Wolbachia is the most widespread endosymbiont, infecting >20% of arthropod species, and capable of drastically manipulating the host’s reproductive mechanisms. Conventionally, diagnosis has relied on PCR amplification; however, PCR is not always a reliable diagnostic technique due to primer specificity, strain diversity, degree of infection and/or tissue sampled. Here, we look for evidence of Wolbachia infection across a wide array of arthropod species using a bioinformatic approach to detect the Wolbachia gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 152 publications
(138 reference statements)
3
64
1
Order By: Relevance
“…Our interpretation is in line with a recent discovery of a highly prevalent supergroup B Wolbachia strain, distinct from other supergroup B strains, in Anopheles “species A” (31). Our phylogenomic reconstructions further support this, as they place the newly assembled Wolbachia genome (33) within supergroup B, but separate from most other strains of this lineage (Fig. S1C).…”
Section: Molecular Evidence For Natural Wolbachia In Anopheles Gambiaesupporting
confidence: 72%
See 1 more Smart Citation
“…Our interpretation is in line with a recent discovery of a highly prevalent supergroup B Wolbachia strain, distinct from other supergroup B strains, in Anopheles “species A” (31). Our phylogenomic reconstructions further support this, as they place the newly assembled Wolbachia genome (33) within supergroup B, but separate from most other strains of this lineage (Fig. S1C).…”
Section: Molecular Evidence For Natural Wolbachia In Anopheles Gambiaesupporting
confidence: 72%
“…Here, we examine the evidence on natural Wolbachia infections in Anopheles gambiae mosquitos and screen 1000 Anopheles genomes ( Ag1000G) project data (32) to reveal that Wolbachia reads are extremely rare in this rich and randomized dataset. We re-analyze the data from which a genome of the putative Wolbachia endosymbiont of Anopheles gambiae was assembled (33) to show that the majority of reads in the sample originate from known Wolbachia hosts different than Anopheles gambiae . Finally, we discuss the requirements to diagnose a Wolbachia infections in a species previously considered uninfected, the potential ecological interactions which could lead to the observed Wolbachia sequence prevalence patterns, and their relevance for the design of successful, integrative approaches to limit malaria spread.…”
Section: Introductionmentioning
confidence: 99%
“…Wolbachia infection was widely distributed in arthropods, and bioinformatics approach was essential for sequencing of Wolbachia strains which showed that most of Wolbachia belongs to subgroup A or B in most of arthropods (Pascar & Chandler, 2018). Wolbachia infection was widely distributed in arthropods, and bioinformatics approach was essential for sequencing of Wolbachia strains which showed that most of Wolbachia belongs to subgroup A or B in most of arthropods (Pascar & Chandler, 2018).…”
Section: Establishment Of Infected and Uninfected Wolbachia Spidersmentioning
confidence: 99%
“…(11, 12)). Successful de novo assembly 48 of complete Wolbachia genomes directly from unenriched long-read sequences also 49 demonstrates that it is unnecessary to computationally filter symbiont reads from 50 host reads based on similarity to Wolbachia reference genomes prior to assembly 51 (13,14). As the cost of long-read sequencing decreases, we argue that direct sequencing…”
mentioning
confidence: 98%